2011
DOI: 10.1007/s11676-011-0153-0
|View full text |Cite
|
Sign up to set email alerts
|

Screening Azadirachta indica tree for enhancing azadirachtin and oil contents in dry areas of Gujarat, India

Abstract:  Azadirachta indica seed samples were collected from four different agro-ecological regions (AERs) viz., AER-2, AER-4, AER-5A and AER-5B of Gujarat state, India during 2000 to 2002 with an aim to assess variability in azadirachtin, oil and fatty acids content of the seeds and assess correlation of these parameters with morphological characters.Azadirachtin, oil and fatty acids content indicated significant (p<0.01) variations between years and AERs in Gujarat. The azadirachtin ranged from 142 to 9 527 μg⋅g -1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Although higher contents of AZA are generally observed in seeds, those values exhibit discrepancy and have been reported in several studies [3,6,7]. This variation results from the fact that the development process of Neem trees is influenced by a myriad of factors, namely geographic area, climate, genetic variability, agronomic conditions, plant morphology and physiology, collection and storage of plant material [30][31][32]. Kaushik et al [31] and Tomar et al [32] analyzed trees from different regions of India and significant differences were observed in the AZA content of seeds collected in different regions.…”
Section: Azadirachtinmentioning
confidence: 99%
See 1 more Smart Citation
“…Although higher contents of AZA are generally observed in seeds, those values exhibit discrepancy and have been reported in several studies [3,6,7]. This variation results from the fact that the development process of Neem trees is influenced by a myriad of factors, namely geographic area, climate, genetic variability, agronomic conditions, plant morphology and physiology, collection and storage of plant material [30][31][32]. Kaushik et al [31] and Tomar et al [32] analyzed trees from different regions of India and significant differences were observed in the AZA content of seeds collected in different regions.…”
Section: Azadirachtinmentioning
confidence: 99%
“…This variation results from the fact that the development process of Neem trees is influenced by a myriad of factors, namely geographic area, climate, genetic variability, agronomic conditions, plant morphology and physiology, collection and storage of plant material [30][31][32]. Kaushik et al [31] and Tomar et al [32] analyzed trees from different regions of India and significant differences were observed in the AZA content of seeds collected in different regions. Furthermore, Kaushik et al [31] evaluated the effect of climatic conditions in the AZA content of seeds and observed that the AZA values of samples retrieved from semi-arid regions subject to mild winters were statistically different from the values observed in hot sub-humid, hot arid and hot semi-arid with cold winter regions.…”
Section: Azadirachtinmentioning
confidence: 99%
“…Kaushik et al 56 . and Tomar et al 57 . independently, analysed trees from different regions of India and observed significant difference in the AZA content of seeds collected in different regions.…”
Section: Introductionmentioning
confidence: 91%
“…Important factors that affect quantities include, among others, neem seeds collected from different geographic regions, timing of collection of seeds, climate, genetic diversity, variations in plant morphological structures and physiology, and storage of neem tree parts [17,76,77]. Kaushik et al [78] and Tomar et al [79] reported comparable variations in the azadirachtin composition of neem seeds collected from different regions of India. Chemical characterization from collected plant parts is inevitable to get reproducible results.…”
Section: Plos Onementioning
confidence: 99%